PENGARUH REWARD DAN BUDAYA ORGANISASI TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) DI KANTOR KEMENTERIAN AGAMA KOTA LUBUKLINGGAU - Amrullah Amrullah; Sardiyo Sardiyo (LPPM UNIVERSITAS BINA INSAN, 2017)
This study aims to find the answer whether there is influence Reward and Organizational Culture Against Performance of Aparatur Sipil Negara (ASN) at the Office of the Ministry of Religious City Lubuklinggau. Based on t test recapitulation for Reward variable has significant influence to apparatus performance with tcount value 2,440> ttable 2,028 and sig value 0,020 <0,05. While recapitulation of t test for organizational culture variable has significant influence to apparatus performance with tcount value 5.302> ttable 2.028 and sig 0,000 <0,05. The results of research calculations conducted in the field showed that Reward and Organizational Culture has a significant effect on apparatus with correlation coefficient obtained the value of R is 0.877 which means the relationship between Reward variable and Organizational Culture shows a strong relationship. Then Reward and Culture Organization together significant effect on performance with value Fcount = 54,884> Ftable = 3,26 with significant level sig = 0,000 <α = 0,05. 95% significant level and a = 5% and db denominator = nk-1 = 36 - 2 - 1 = 33 and the db of the numerator k = the number of variables - 1 (k = 2) which means Reward and Organizational Culture variables simultaneously have a significant influence on ASN Performance Office of the Ministry of Religious Affairs of Lubuklinggau City.